2010
DOI: 10.1186/1465-9921-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxygen partial pressure of brain tissue in an animal model of obstructive apnea

Abstract: BackgroundCognitive impairment is one of the main consequences of obstructive sleep apnea (OSA) and is usually attributed in part to the oxidative stress caused by intermittent hypoxia in cerebral tissues. The presence of oxygen-reactive species in the brain tissue should be produced by the deoxygenation-reoxygenation cycles which occur at tissue level during recurrent apneic events. However, how changes in arterial blood oxygen saturation (SpO2) during repetitive apneas translate into oxygen partial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Assessment of the changes in PaO 2 induced by intermittent hypoxia exposure in the bowel was carried out with an oxygen sensor that was previously used to measure PaO 2 within different tissues in animal models of OSA [4,6]. As expected, the level of oxygenation in the faeces decreased as the sensor approached the anoxic core of the intestinal content.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Assessment of the changes in PaO 2 induced by intermittent hypoxia exposure in the bowel was carried out with an oxygen sensor that was previously used to measure PaO 2 within different tissues in animal models of OSA [4,6]. As expected, the level of oxygenation in the faeces decreased as the sensor approached the anoxic core of the intestinal content.…”
Section: Discussionmentioning
confidence: 86%
“…Whereas the magnitude and pathophysiological impact of hypoxia/re-oxygenation has been investigated in different organs and tissues such as brain, liver, testes, fat or muscle [4][5][6], no attention has been paid to the potential effect of recurrent oxygen desaturations that characterise OSA on the gut microbiota. In fact, the mammalian gut is populated by a complex and dense microbial community dominated by obligate anaerobic organisms from both the Firmicutes and Bacteroidetes phyla in a dynamic environment determined by the host physiology [7].…”
Section: Introductionmentioning
confidence: 99%
“…Such changes may be able to influence neuron excitability that is sensitive not only to hypoxia but also to changes in arterial CO 2 and circulating ions such as bicar- all et al 2010) as well as personal observations (unpublished data) regarding cortex oxygenation assessed with near-infrared spectroscopy in healthy subjects inhaling a hypoxic gas mixture at rest indicated that the kinetics of cortex deoxygenation response is noticeably longer than arterial blood deoxygenation, requiring Ͼ20 -30 min to reach a steady state. Also, recent animal studies regarding brain oxygenation under hypoxemic conditions emphasize the specificity of brain tissue oxygenation response to hypoxemia, with, for instance, some cerebral reoxygenation being observed over the course of a 1-h stable periodic pattern of hypoxemia (Almendros et al 2010). Therefore, the specific pattern of cerebral tissue deoxygenation under hypoxemic conditions could contribute to a time-dependent effect of hypoxic breathing on cortex excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Almendros and colleagues [27,28] have recently examined changes in oxygen partial pressure of brain tissue (PtO 2 ) in an animal model of obstructive apnea. The model is designed to apply recurrent obstructive apneas in a stable and controlled way without other comorbidities that can occur in OSA.…”
Section: Discussionmentioning
confidence: 99%